Dynamical nuclear decoupling of electron spins in molecular graphenoid radicals and biradicals - Lombardi, Federico; Myers, William K.; Ma, Ji; Liu, Junzhi; Feng, Xinliang; Bogani, Lapo (Physical Review B, 2020)
We investigate the mechanisms of nuclear decoupling in synthetically tailored graphenoids, where the electron spin state is introduced by topological manipulation of the lattice. We compare molecular graphenoids containing one and two spin centers, introduced by pentagonal rings in the honeycomb lattice. Exploiting the molecular nature of the systems, we investigate the role of different nuclear species and environments. Variations on the Carr-Purcell-Meiboom-Gill pulse trains are used to prolong the coherence time of the electron spin of the radicaloids, leading to substantial improvements in performance and coherence times up to 300 μs at liquid-nitrogen temperature. The investigation of electron spin coherence as a function of interpulse spacing, with times close to the inverse of the nuclear precession frequency, reveals that a train of pulses in phase with the nuclear precession maximizes the nuclear decoupling. At room temperature the limits imposed by the sample treatment and environment are reached, indicating what amelioration is necessary to further enhance the quantum performance.
CRIS-Team Scopus Importer:2023-03-20